Schedule Planning and Maintenance Activities Auxiliary Power Unit (APU) Boeing 737-500 Aircraft With Reliability Method - Ferry Setiawan; Yustina Titin Purwantiningsih; Dhimas Wicaksono (Akademi Angkatan Udara, 2021)
This study aims to plan effective maintenance schedules and activities on the auxiliarypower unit system so that there will be no more failures or unplanned or sudden damage. Failures in auxiliary power unit equipment often occur in several work systems, namely electrical systems, lubrication systems and Ignition systems, where this causes considerable losses for airlines. This research method uses qualitative and quantitative approaches, qualitative analysis uses the Failure Mode Effect and Critically Analysis (FMECA) method by analyzing the factors causing failure and the effects of failure, with the results of the causes of failure in several auxiliary power unit (APU) work systems as follows: the following electrical system is on the Relay start component, the Lubrication System is on the Oil Filter component, the Ignition System is on the igniter plug. From the results of the FMECA analysis, a quantitative analysis was carried out with the analysis carried out using the reliability method, the reliability parameter was calculated by the Weibull probability distribution, to determine the critical limit of the operational time of the component or system part which is the reliability limit of an auxiliary power unit system. The critical operational limit for the electrical system is 434 flight hours, the lubrication system is 1186 flight hours, and the Ignition system is 1610 flight hours, then these results are used to determine an effective maintenance schedule supported by planning the right maintenance activities to eliminate the causes - cause of failure in auxiliary power unit equipment.